2018
DOI: 10.21767/2574-2817.100006
|View full text |Cite
|
Sign up to set email alerts
|

Sun Protection Read-Along Books: Assessing the Feasibility of Delivering the Intervention in Pediatrician’s Offices

Abstract: Background: Sun exposure, particularly during childhood, is an important contributing factor in developing melanoma later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The systematic literature review identified nine manuscripts. Four of these described books focused on natural disasters including typhoons, hurricanes and storms ( Sharpe and Izadkhah, 2014 ; Marvida and Tibayan, 2019 ; McKeon, 2020 ; Solfiah et al ., 2020 ), and five related to health messaging including sun safety and juvenile idiopathic arthritis ( Thornton and Piacquadio, 1996 ; McDermott and Lowe, 2003 ; Armstrong, 2012 ; Egert et al ., 2017 ; Robinson et al , 2017 ). None of the identified manuscripts described the development of books for children relating specifically to bushfires or bushfire smoke.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic literature review identified nine manuscripts. Four of these described books focused on natural disasters including typhoons, hurricanes and storms ( Sharpe and Izadkhah, 2014 ; Marvida and Tibayan, 2019 ; McKeon, 2020 ; Solfiah et al ., 2020 ), and five related to health messaging including sun safety and juvenile idiopathic arthritis ( Thornton and Piacquadio, 1996 ; McDermott and Lowe, 2003 ; Armstrong, 2012 ; Egert et al ., 2017 ; Robinson et al , 2017 ). None of the identified manuscripts described the development of books for children relating specifically to bushfires or bushfire smoke.…”
Section: Resultsmentioning
confidence: 99%
“…All manuscripts indicated their primary target audience was children, with age ranges of 2–3 years (as in McDermott and Lowe, 2003 ), 2–6 years (as in Robinson et al ., 2017 ), 5–6 years (as in Solfiah et al ., 2020 ), 5–8 years (as in Armstrong, 2012 ), 8–9 years (as in Thornton and Piacquadio, 1996 ), and the remainder not specifying a specific age range ( Egert et al , 2017 ; Marvida and Tibayan, 2019 ; McKeon, 2020 ). Most authors interviewed who discussed the target age group noted the age ranges of their works were typically dictated by their publisher.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations